Children, families and schools : developing partnerships for inclusive education - Beveridge, Sally (RoutledgeFalmer, 2005)
This book is concerned with home-school relations from an 'inclusive'perspective, in that it addresses questions common to all schools, but with an emphasis on children with special needs.- Resumé vydavatel
Keywords: integrovaná výchova a vzdělávání -- Velká Británie; rodina a škola -- Velká Británie; děti se zdravotním postižením -- Velká Británie; speciální pedagogika -- Velká Británie; integrated education -- Great Britain; home and school -- Great Britain; children with disabilities -- Great Britain; special education -- Great Britain; elektronické knihy; monografie; electronic books; monographs